Mosques as Islamic Social Infrastructure for Community Resilience in Tsunami-Prone Padang, Indonesia - Narny, Yenny (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2026)
This article examines the potential of mosques to function as Islamic social infrastructure for strengthening community resilience in tsunami-prone coastal Padang, Indonesia. Existing disaster risk reduction strategies in Padang have largely emphasised technical mitigation, early warning systems, evacuation routes, and purpose-built vertical evacuation shelters. However, the limited number and uneven distribution of formal shelters remain critical problems, especially in densely populated coastal areas exposed to short tsunami arrival times. Rather than treating mosques merely as religious buildings or informal refuge spaces, this article repositions them as socially trusted, spatially embedded, and culturally legitimate institutions that can support community-based disaster preparedness. The study employs a qualitative evidence synthesis approach, drawing on secondary spatial data, disaster risk studies, mosque distribution data, and literature on social trust, place attachment, Islamic perspectives on disaster, and community resilience. The findings show that mosques in coastal Padang possess four strategic qualities: spatial proximity to exposed communities, everyday familiarity, moral legitimacy, and institutional capacity for collective coordination. By integrating these qualities into disaster planning, mosques can become community-based nodes of preparedness, evacuation, communication, and post-disaster support. This article contributes to disaster risk reduction and Islamic social studies by developing the concept of mosque-based Islamic social infrastructure as a culturally grounded framework for resilience in Muslim coastal communities.